The first national data of Turkish pre-hospital emergency care for children: Epidemiology, clinical characteristics, and outcomes. Issue 5 (September 2022) - Turan, Caner; Saz, Eylem Ulas; Anil, Murat; Bal, Alkan; Gokalp, Gamze; Yilmaz, Hayri Levent; Sari Gokay, Sinem; Celik, Tugce; Tuygun, Nilden; Akca, Halise; Tekin, Deniz; Oguz, Sinan; et al.
Background and Objectives: The emergency medical service system is designed to ensure rapid identification and transport of patients from the field to emergency departments. This study aims to examine pediatric patients' clinical characteristics and reasons for ambulance use in Turkey. Life-saving interventions and non-life-saving interventions performed during transport and patients' outcomes following transport were also investigated. Methods: This is a prospective-multicentric study conducted at four metropolitan cities and nine tertiary pediatric emergency departments. This survey-based study evaluated all children brought by ambulance to emergency departments. Patient demographics, clinical features, triage levels, procedures performed in the ambulance or emergency department, and final outcomes were sought. Results: A total of 2094 patients were transported during the study period. Only a minority of ambulances were physician staffed (16.5%), and 72% of the patients were delivered to pediatric emergency departments without notification calls. Although notification calls were more likely given for particularly critically ill children, for non-urgent conditions transfer calls were less common (60.8% vs 23.5%, respectively; p < 0.001). A majority of transports were performed for trauma patients (20.5%), neurological issues (20%), and toxicological emergencies (13.8%). While parents prefer using the ambulances for medical emergencies, physicians prefer it for mainly traumatic and toxicological emergencies. In total, 65% of the patients received at least one intervention, and 18 patients needed immediate life-saving interventions (intubation, cardiopulmonary resuscitation, etc.) but they did not receive it. Mortality occurred in nine patients. If the health care providers were paramedics, they were more likely avoided by performing any intervention in critically ill children ( p < 0.001). A majority of the procedures performed in children were older than 12 months ( p < 0.001). Conclusion: This study presents comprehensive epidemiological and outcome data for pediatric patients transported by the national emergency medical service system in Turkey. Non-urgent calls were more likely made by parents, physicians avoided making NCs, and paramedics also avoided performing any intervention when they were transporting children.